The current landscape of European registries for rare endocrine conditions. Issue 1 (January 2019) - Ali, S R; Bryce, J; Cools, M; Korbonits, M; Beun, J G; Taruscio, D; Danne, T; Dattani, M; Dekkers, O M; Linglart, A; Netchine, I; Nordenstrom, A; et al.
Abstract : Objective: To identify cross-border international registries for rare endocrine conditions that are led from Europe and to understand the extent of engagement with these registries within a network of reference centres (RCs) for rare endocrine conditions. Methods: Database search of international registries and a survey of RCs in the European Reference Network for rare endocrine conditions (Endo-ERN) with an overall response rate of 82%. Results: Of the 42 conditions with orphacodes currently covered within Endo-ERN, international registries exist for 32 (76%). Of 27 registries identified in the Orphanet and RD-Connect databases, Endo-ERN RCs were aware of 11 (41%). Of 21 registries identified by the RC, RD-Connect and Orphanet did not have a record of 10 (48%). Of the 29 glucose RCs, the awareness and participation rate in an international registry was highest for rare diabetes at 75 and 56% respectively. Of the 37 sex development RCs, the corresponding rates were highest for disorders of sex development at 70 and 52%. Of the 33 adrenal RCs, the rates were highest for adrenocortical tumours at 68 and 43%. Of the 43 pituitary RCs, the rates were highest for pituitary adenomas at 43 and 29%. Of the 31 genetic tumour RCs, the rates were highest for MEN1 at 26 and 9%. For the remaining conditions, awareness and participation in registries was less than 25%. Conclusion: Although there is a need to develop new registries for rare endocrine conditions, there is a more immediate need to improve the awareness and participation in existing registries.